A review of the predictors of antimicrobial use and resistance in European food animal production - Redman-White, Carys J.; Moran, Dominic; Peters, Andrew R.; Muwonge, Adrian (Frontiers in Antibiotics, 2023)
Antimicrobial resistance (AMR) is a major threat to global health and a key One Health challenge linking humans, animals, and the environment. Livestock are a key target for moderation of antimicrobial use (AMU), which is a major driver of AMR in these species. While some studies have assessed AMU and AMR in individual production systems, the evidence regarding predictors of AMU and AMR in livestock is fragmented, with significant research gaps in identifying the predictors of AMU and AMR common across farming systems. This review summarizes existing knowledge to identify key practices and critical control points determining on-farm AMU/AMR determinants for pigs, layer and broiler hens, beef and dairy cattle, sheep, turkeys, and farmed salmon in Europe. The quality and quantity of evidence differed between livestock types, with sheep, beef cattle, laying hens, turkeys and salmon underrepresented. Interventions to mitigate both AMU and/or AMR highlighted in these studies included biosecurity and herd health plans. Organic production typically showed significantly lower AMU across species, but in antibiotic-free systems, varying AMR levels were identified in livestock microflora. Although vaccination is frequently implemented as part of herd health plans, its effects on AMU/AMR remain unclear at farm level. Social and behavioral factors were identified as important influences on AMU. The study fills a conspicuous gap in the existing AMR and One Health literatures examining links between farm management practices and AMU and AMR in European livestock production.